Leukopenia in Kidney Transplant Patients with the Association of Valganciclovir and Mycophenolate Mofetil - Brum, S (2008)
Cytomegalovirus (CMV) is the most common viral infection after transplantation. Valganciclovir (VGC) is established for prophylaxis and treatment of CMV infections, but leukopenia which appears in 10% to 13% (severe in 4.9%) is the principal side effect. We have recently noted an increased incidence of leukopenia and severe neutropenia among our renal transplant patients and thought to identify the associated factors. We conducted a retrospective analysis of all kidney transplantations performed between January 2005 and December 2006. All patients received mycophenolate mofetil (MMF), tacrolimus, and steroids. VGC was used for targeted prophylaxis and preemptive therapy of CMV infection, with doses adjusted to renal function. Of the 64 patients undergoing renal transplantation 13 (20.3%) developed leukopenia within 3 +/- 2 months after transplantation with severe neutropenia in 5 (7.8%). All patients were on MMF and VGC (VGC 605 +/- 296 mg/d). Leukopenia was significantly associated with simultaneous liver-kidney transplantation and with second kidney transplantations (P < .01). The incidence of leukopenia was higher among patients under VGC since day 1 of transplantation (P = .008) with maximal incidence observed among patients prescribed 900 mg/d as opposed to those on lower doses (P < .01). There was no increase in CMV infection among patients with a low dose of VGC. No patient developed clinical CMV disease. In conclusion, VGC prophylaxis was associated with an increased frequency of leukopenia on MMF-tacrolimus treated patients or regimens. Low-dose VGC for CMV prophylaxis appeared to be as effective as high-dose treatment, and associated less frequently with leukopenia and neutropenia.